Impact of Social Background on Pupils career decision-making in transition to upper secondary education - Petr Hlaďo (Pedagogická Orientace, 2010)
The transition of pupils between lower and upper secondary educationrepresents a crucial phase in one’s life and is connected with several critical moments.Whether the chosen educational and career pathway correlates with his or hercapabilities and interests, it is crucial both to nurture positive growth, achieve personalsatisfaction and success, and realize his or her full potential. The advances synthesiseconclusions of selected researches conducted largely in anglo-american countries andin the Czech Republic. A particular attention has been paid to the impact of socialbackground on the pupils’s career choice, rate of autonomy in the decision-makingprocess, applied parental strategies, forming educational and occupational aspirationsof pupils and other research problems.